Роль Володимира Іполитовича Липського в розробці наукових основ створення ботанічного саду АН УРСР - Chuvikina, N.V.; Cherevchenko, T.M.; Kvasha, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The present paper elucidation the role of famous scientist Volodimir I. Lipsky in the development of scientific principles for creation of Botanical Garden of Ukrainian Academy of Sciences.